If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6y+3y-9=90
We move all terms to the left:
6y+3y-9-(90)=0
We add all the numbers together, and all the variables
9y-99=0
We move all terms containing y to the left, all other terms to the right
9y=99
y=99/9
y=11
| X2-23x+126=0 | | 15x–24=3x | | 5x+9x+8=180 | | 12(x+5)=114 | | 8x-2+4x+26=180 | | 3x+12+5x+6=90 | | p-7/3=-12 | | (2x+16)+(4x+3)=35 | | 3x-3(4-5x)=3(x-9) | | 1/10y=y+18 | | 15─2m=13 | | 5m^2=22m+15 | | m-1/4=-2 | | 34−(2c+4)=2(c+5)c | | m/7+7=-1 | | (2x-5)÷3=(5x-3)÷5 | | -3(y-3)=-7y+17 | | x+4x+14=244 | | X+2x-11=23 | | y+(–10)=6 | | 3n+1=33 | | 2(5-x)=25-2(3x-0,5) | | 4+3x=2x-7 | | 3(×-6)=2(x+6) | | 13x-11=2x | | 4x-5=9+6x | | 3*x+2=4 | | 100y+70+0=114y | | 2m-5m=-7+9 | | 3m^2-12m-20=0 | | R*2-21r+80=0 | | 65=(3a-2)*a |